Heat Waves/cold Waves Trends and Agricultural Impact in Mid Hills of Himachal Pradesh - Jattan, Priyanka; Singh, Mohan; Bhardwaj, S. K. (International Journal of Bio-resource and Stress Management, 2026)
The analysis was carried out from 1984–2023 at Dr. Y. S. Parmar UHF, Nauni, using secondary data to examine heat-wave and cold-wave trends and their agricultural impact in the mid-hills of Himachal Pradesh. The variability of Heat waves and cold waves depends on local climatic and geographical conditions. Daily maximum and minimum temperature and relative humidity data were obtained from the Agrometeorological Observatory at Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Solan, while crop yield data were collected from the Department of Horticulture. Events of heat wave, severe heat wave, cold wave, severe cold wave, and the heat index were identified and analyzed for monthly, annual, and decadal variability. The annual mean maximum and minimum temperatures were 25.4°C and 11.6°C, with relative humidity averaging 60%. The maximum and minimum temperatures and relative humidity increased by 2.5°C, 0.55°C, and 1.07% year-1, respectively. In total, 669 heat waves, 161 severe heat waves, 260 cold waves, and 37 severe cold waves were recorded. Heat waves increased by 1.11 events year-1, while cold waves decreased by 2.86 events year-1. Both rising and declining extremes adversely affected crop yields. The heat index showed a rising trend, indicating regional warming. These findings emphasize the need for adaptive strategies and a better understanding of extreme temperature events to safeguard agricultural production under climate change.